2019
DOI: 10.1109/tits.2018.2799228
|View full text |Cite
|
Sign up to set email alerts
|

BoxCars: Improving Fine-Grained Recognition of Vehicles Using 3-D Bounding Boxes in Traffic Surveillance

Abstract: In this paper, we focus on fine-grained recognition of vehicles mainly in traffic surveillance applications. We propose an approach that is orthogonal to recent advancements in finegrained recognition (automatic part discovery, bilinear pooling). Also, in contrast to other methods focused on fine-grained recognition of vehicles, we do not limit ourselves to a frontal/rear viewpoint, but allow the vehicles to be seen from any viewpoint. Our approach is based on 3D bounding boxes built around the vehicles. The b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 68 publications
1
70
0
1
Order By: Relevance
“…Sochor et al are noted for collecting the BoxCars [64] and BoxCars116k [65] datasets. In [64], the recognition performance is boosted by inserting additional supplementary information to the neural network, more specifically, 3D vehicle bounding box, rasterized low-resolution shape, and 3D vehicle orientation.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Sochor et al are noted for collecting the BoxCars [64] and BoxCars116k [65] datasets. In [64], the recognition performance is boosted by inserting additional supplementary information to the neural network, more specifically, 3D vehicle bounding box, rasterized low-resolution shape, and 3D vehicle orientation.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…In one case, Sochor et al proposed a model constructing 3-D bounding boxes around vehicles through the use of convolutional neural networks (CNNs) from only a single camera viewpoint. This makes it possible to project the coordinates of the car from an oblique viewpoint to dimensionally-accurate space [16]. Likewise, Hussein et al tracked pedestrians from two hours of video data from a major signalized In the second module, we extract various features frame-by-frame, such as vehicle velocity, vehicle acceleration, pedestrian velocity, the distance between vehicle and pedestrian, and the distance between vehicle and crosswalk.…”
Section: Preprocessingmentioning
confidence: 99%
“…There are datasets of vehicles (Krause et al, 2013;Yang et al, 2015;Sochor et al, 2017), which are created for finegrained recognition with annotations on several attributes such as type, make and color. However, the identities of the vehicles in the datasets are not known; thus, the datasets are not directly applicable for vehicle re-identification, especially for evaluation.…”
Section: Vehicle Re-identification Datasetsmentioning
confidence: 99%
“…For feature extraction from images we use Inception-ResNet-v2 (Szegedy et al, 2017) with images resized to 331 × 331 yielding feature vectors with length 1536 for each input image. Sochor et al (2016Sochor et al ( , 2017 showed that unpacking the input vehicle by 3D bounding box and alternating the input image colors is beneficial for fine-grained recognition of vehicles; we use these modifications for re-identification of vehicles as well.…”
Section: Vehicle Re-identificationmentioning
confidence: 99%